Characterization in Ancient Greek Literature : Studies in Ancient Greek Narrative, Vol. 4 - De,Temmerman, Koen (Mnemosyne, Supplements Ser, 2017)
"âContents" -- "âPreface" -- "âNote on Citation and Abbreviations" -- "âGlossary" -- "âCharacter and Characterization in Ancient Greek Literature: An Introduction (De Temmerman and van Emde Boas)" -- "âPart 1. Epic and Elegiac Poetry" -- "âChapter 1. Homer (de Jong)" -- "âChapter 2. Hesiod (Koning)" -- "âChapter 3. The Homeric Hymns (de Jong)" -- "âChapter 4. Apollonius of Rhodes (Klooster)" -- "âChapter 5. Callimachus (Harder)" -- "âChapter 6. Theocritus (Klooster)" -- "âPart 2. Historiography" -- "âChapter 7. Herodotus (de Bakker)" -- "âChapter 8. Thucydides (Rood)" -- "âChapter 9. Xenophon (Rood)" -- "âChapter 10. Polybius (Pitcher)" -- "âChapter 11. Appian (Pitcher)" -- "âChapter 12. Cassius Dio (Pitcher)" -- "âChapter 13. Herodian (Pitcher)" -- "âChapter 14. Josephus (van Henten and Huitink)" -- "âChapter 15. Pausanias (Pretzler)" -- "âPart 3. Choral Lyric" -- "âChapter 16. Pindar and Bacchylides (Currie)" -- "âPart 4. Drama" -- "âChapter 17. Aeschylus (van Emde Boas)" -- "âChapter 18. Sophocles (Lloyd)" -- "âChapter 19. Euripides (van Emde Boas)" -- "âChapter 20. Aristophanes (Bowie)" -- "âChapter 21. Menander (Brown)" -- "âPart 5. Oratory" -- "âChapter 22. Lysias (de Bakker)" -- "âChapter 23. Aeschines and Demosthenes (Worman)" -- "âPart 6. Philosophy" -- "âChapter 24. Plato (Morgan)" -- "âPart 7. Biography" -- "âChapter 25. Xenophon (Huitink)" -- "âChapter 26. Plutarch (Mossman)" -- "âChapter 27. Philostratus (Demoen)" -- "âPart 8. Between Philosophy and Rhetoric" -- "âChapter 28. Dio Chrysostom (Kasprzyk)" -- "âChapter 29. Lucian (Hodkinson)" -- "âPart 9. The Novel" -- "âChapter 30. Chariton (De Temmerman)" -- "âChapter 31. Xenophon of Ephesus (De Temmerman)" -- "âChapter 32. Achilles Tatius (De Temmerman)" -- "âChapter 33. Longus (Morgan)".